A study on waveband routing optical networks employing waveband selective switch-based cross-connects - Tien Ban, Nguyen; Hai Chau, Le (Vietnam Journal of Science and Technology, 2017)
A waveband cross-connect architecture is proposed, utilizing small-scale wavebandselective switches to make the best use of present optical switch technologies and exploit opticalwaveband switching for creating cost-effective large capacity optical path networks. Anappropriate network design algorithm is then developed for the waveband routing opticalnetworks employing the waveband cross-connect architecture. Numerical experiments prove thatapplying the small-scale waveband selective switch-based node architecture offers a significantswitch scale reduction. The effect of the waveband capacity selection on the overall switch scalereduction was also investigated.